Mechanisms Forming Negative Curvature Spectra of Discrete Decameter Radio Sources - Tsvyk, N. A. (Видавничий дім «Академперіодика», 2013)
Mechanisms Forming Negative Curvature Spectra of Discrete Decameter Radio Sources